O PRONAF e os seus reflexos para a agricultura familiar - Fardin, Merci Pereira (2014)
This study aims to uderstand the role of the state in the formulation of agricultural policies that drive the development of the capitalist mode of production in agriculture, through the study of the agricultural modernization, focusing on the 1965-2012 period. We used, as a source of research, secondary data from government and supranational agencies, as well as authors with a history in the study of the topic, in order to demonstrate the peculiarities of development of capitalism in agriculture of underdeveloped country with a dependent economy. Hence, it is necessary to understand the control exerted by foreign capital on strategic links of the economy, the perpetuation of social segregation and the over-exploitation of labor as the basis of national society. We concluded that the National Program for Strengthening Family Agriculture (PRONAF), agricultural policy that was created in the mid-1990s for small producers, has been promoting deeds similar to those of the agricultural policy formulated by the State during the military regime, which was classified as conservative modernization. In this sense, PRONAF presents the strategy to fit family farmers in the paradigms of production efficiency, resulting in the segregation between those apt (competitive) and those inapt for survival in the market.